The effect of financial development on economic growth in high-income countries - Ikhsan, Akmil; Satrianto, Alpon (Asian Economic and Financial Review, 2023)
This study aims to analyze the effect of financial development on economic growth high-income countries. To support the results of this study, the variables used are financial development from the institutional and market side, as well savings and investment. Through the panel data method using the fixed effects model (FEM) approach. The results of study show that financial development has an effect on economic growth high-income countries. This research emphasizes that financial development can encourage economic growth for countries that focus on building a strong financial sector by mobilizing capital, which is a necessity for economic activity. Especially from the perspective of financial institutions and markets, financial development must become the basis for formulating policies so that it will have an impact on the absorption and distribution of financial resources and become an important factor in driving economic growth. In addition, savings and investment are channels to meet the needs of financial resources and must be maintained so that they can contribute to economic growth. With these results, the governments of high-income countries can strengthen policy in the financial sector so that it becomes the foundation for economic growth.